The common mistakes in combating terrorism financing - Zul Kepli, Mohd Yazid (Zes Rokman Resources, 2016)
The growing threat of terrorism has reached a serious level. During 2015, a series of terrorist attacks is recorded in France, Pakistan, Chad, Tunisia, Kuwait, Kenya, and Yemen. The danger of terrorism is amplified many times if state terrorism is also taken into account. Estimates of death in the Syrian Civil War vary between 301,781 and 470,000. According to the United Nations and Arab League Envoy to Syria, the estimates of death are more than 400,000. A significant number of these deaths refer to unarmed civilians caught in conflict. To stop terrorism, it is essential to combat the financing of terrorism. The bloodline of terrorist networks is said to be money. Although terrorism can inflicts the largest amount of damage using minimum cost, it still needs money. While bribery, weapons and the maintenance of weapons are major expense, other security costs including operating costs, false identification and other concealment mechanisms also require money. In addition, networking, communications and the training of personnel and maintaining training camps are not cheap. However, addressing the symptoms alone is inadequate. It is important to effectively eradicate the root causes of terrorism, together with the sources of financing to ensure global peace. This article highlights the common mistakes in combating terrorism financing by focusing on Islamophobia, Islamic finance and Islamic charities. The common methods of terrorism financing will be discussed together with the flaws and the way forward.